Measurements of sex-related differences in maxillary sinus and mandibular canal characteristic using cone beam computed tomography. (June 2020) - Waluyo, Rina Fajarwati; Priaminiarti, Menik; Yuniastuti, Mindya; Soedarsono, Nurtami; Susilo, Bambang Tri
Highlights: Cone beam computed tomography can visualize the maxillary sinus and the mandibular canal. The height, length, and width of the maxillary sinus showed significant differences between men and women. The distance from the mandibular canal to the inferior border of the mandible showed significant differences between men and women. Abstract: Background: Methods for human identification, including sex determination, must enable the examination of severely burned, damaged, or decomposed bodies. Maxillofacial structures that can be used to determine sex include the maxillary sinus and mandibular canal. Cone beam computed tomography (CBCT) is a non-invasive, high-resolution method that can visualize maxillofacial anatomy, including the maxillary sinus and the mandibular canal. CBCT provides detailed measurements of any anatomical structure for forensic identification. Aim: To evaluate the usefulness of a method to determine sex based on maxillary sinus size and mandibular canal position. Methods: The height, length, and width of the maxillary sinus and the distances from the mandibular canal to the buccal, lingual, and inferior borders of the mandible were measured in 138 samples using Digital Image Communication in Medicine-compatible Carestream 3D Imaging Software©. Logistic regression analysis was performed to identify specific factors for sex determination. Results: The size of the maxillary sinus and the distance from the mandibular canal to the inferior border of the mandible were significantly different between men and women ( p  < 0.05). The mean maxillary sinus height, length, and width of men were 39.4 ± 4.6, 39.9 ± 3.2, and 31.1 ± 4.6 mm, while those of women were 33.9 ± 4.8, 37.4 ± 2.4, and 28.6 ± 3.8 mm, respectively. The mean distances from the mandibular canal to the inferior border of the mandible were 7.7 ± 1.7 mm in men and 6.8 ± 1.5 mm in women. Conclusion: The height, length, and width of the maxillary sinus, as well as the distance from the mandibular canal to the inferior border of the mandible, can be utilized for sex determination via CBCT radiographic imaging.